Left atrial phasic function in older adults is associated with fibrotic and low-grade inflammatory pathways - Koh, Angela S. (2023)
Introduction: Concomitant risk factors challenge the mechanistic understanding of cardiac aging. We determined the degree to which the left atrial function could be distinguished by advanced cardiac magnetic resonance (CMR) imaging in older adults and assessed associations between the left atrial function and the plasma biomarkers related to biological aging and cardiovascular disease [serum monocyte chemoattractant protein-1 (MCP1), matrix metallopeptidase 9 (MMP-9), B-type natriuretic peptides (BNPs), galectin-3 (Gal-3), high-sensitivity cardiac troponin I (hsTn1), high-sensitivity C-reactive protein (hs-CRP), and soluble urokinase plasminogen activator receptor (sUPAR)]. Methods: Among a cross-sectional population-based cohort of older adults, longitudinal LA strain including reservoir strain (ϵs), conduit strain (ϵe), and booster strain (ϵa) as well as peak strain rates (SRs, SRe, SRa) were determined using CMR and studied in association with blood biomarkers. Results: We studied 243 community adults (42.8% female, mean age 70.3 ± 9.5 years). In bivariate analysis, ϵe and SRe were reduced in gradation with increasing risk factors (all p values <0.0001). Corresponding levels of sUPAR (ng/mL) were quantitatively higher in older adults with <2 risk factors (2.5 ± 1.6 vs. 1.7 ± 1.3, p = 0.0005), in those with ≥2 risk factors (3.3 ± 2.4 vs. 1.7 ± 1.3, p < 0.0001), compared to young adults; including between older adults with ≥2 risk factors and older adults with <2 risk factors (3.3 ± 2.4 vs. 2.5 ± 1.6, p = 0.017). Based on multivariate analysis, sUPAR was significantly associated with both ϵe (OR 1.52, p = 0.006) and SRe decline (OR 1.5, p = 0.019). The associations between Gal-3 and ϵe reduction (OR 1.2, p = 0.022) and between BNP and SRe decline were generally weaker (OR 1.03, p = 0.027). The addition of sUPAR to a model consisting of age, risk factors, Gal-3, and BNPs increased the area under the curve of ϵe from 0.72 to 0.77 (p = 0.015). Conclusion: By advanced CMR imaging, a panel of circulating biomarkers comprising galectin, MMP-9 and sUPAR were associated with left atrial dysfunction in older adults. Higher levels of Gal-3 and MMP-9 may be suggestive of fibrotic mechanisms in left atrial aging while impairments in left atrial strain seen in association with circulating sUPAR may be related to immune activation in the left atrium in response to left atrial remodeling and fibrotic processes.